The Product Packaging Design And Advertisement Attraction On Brand Awareness And Its Impact On Repurchasing Teh Botol Sosro Among Young Children At Tangerang City - Siti Asriah Immawati; Rosyid Rosyid (LPPM of NAROTAMA UNIVERSITY, 2018)
Purpose: The purpose of this research was to determine the effect of product packaging design and attractiveness of advertisements on brand awareness on consumers both partially and simultaneously as well as the impact of brand awareness on consumers' interest in re-purchasing Teh Botol Sosro among young people in Tangerang City.. Design/methodology/approach: This is a sampling technique is a sample area. Instrument testing is done by testing the validity and reliability, data analysis techniques using classical assumption test, multiple regression analysis, and hypothesis testing at ? = 0.05. Findings: The results of the research show that: (1) product packaging design influences brand awareness with sig 0,000 (2) ad attractiveness has a positive and significant effect on brand awareness with a sig value of 0,000 (3) product packaging design has a positive and significant effect on repurchase intention consumers with a sig value of 0,000 (4). ad attractiveness does not have a positive and significant effect on consumers' repurchase intention with a value of 0.141 sig (5) product packaging design and ad attractiveness has a positive and significant effect on brand awareness with a sig value of 0.000 (6) product packaging design and ad attractiveness has a positive effect and significant to consumers 'repurchase interest with a sig value of 0,000 (7) brand awareness has a positive and significant effect on consumers' repurchase interest with a sig value of 0,000 Research limitations/implications: The population in this research were all young people in the city of Tangerang, while the sample in this research was 100 (one hundred) Respondents who were in Tangerang District, Cibodas District and Ciledug District who had made a purchase of Teh Botol Sosro beverage. Practical implications: Packaging design is one of the important factors in product sales. If the form and packaging material are standard, then the graphic elements on the packaging can be a determining factor of whether or not a package is attractive. A good packaging design is not only attractive when displayed on a sales shelf but also can convince consumers to buy. Not many of us know that Teh Botol Sosro packaging designs have packaging designs, especially graphic elements that vary in each market. This is interesting to study and analyze because not many tea beverage products have different graphics elements between products marketed in the local market and export.. Paper type: Research paper